2015
DOI: 10.1161/circulationaha.114.012316
|View full text |Cite|
|
Sign up to set email alerts
|

Hck/Fgr Kinase Deficiency Reduces Plaque Growth and Stability by Blunting Monocyte Recruitment and Intraplaque Motility

Abstract: The hematopoietic deficiency of Hck and Fgr led to attenuated atherosclerotic plaque formation by abrogating endothelial adhesion and transmigration; paradoxically, it also promoted plaque instability by causing monocyte subset imbalance and subendothelial accumulation, raising a note of caution regarding src kinase-targeted intervention in plaque inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…The current findings supported the idea that inflammation played a part in the pathophysiological mechanisms involved in ST-segment elevation myocardial infarction (STEMI) [88]. Two recent animal studies demonstrated the role of inflammation and neutrophils in the atherosclerotic process, in healing after myocardial infarction, and in cardiac remodeling [89,90].…”
Section: Hbp In Acute Bacterialsupporting
confidence: 84%
“…The current findings supported the idea that inflammation played a part in the pathophysiological mechanisms involved in ST-segment elevation myocardial infarction (STEMI) [88]. Two recent animal studies demonstrated the role of inflammation and neutrophils in the atherosclerotic process, in healing after myocardial infarction, and in cardiac remodeling [89,90].…”
Section: Hbp In Acute Bacterialsupporting
confidence: 84%
“…Although Hck and Fgr only show overlapping localization at the cell membrane, compound Hck KO ; Fgr KO mice are unable to clear Listeria infection (Lowell et al, 1994), and show blunted recruitment of myeloid cells to arterial plaques or to LPS-challenged lungs (Mazzi et al, 2015; Medina et al, 2015). By contrast, excessive activation of endogenous SFK results in a lethal autoimmune response in Lyn CA mice (Hibbs et al, 1995) and inflammatory lung disease in Hck CA mice (Ernst et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Upon migration into infected tissue, monocytes differentiate into dendritic cells and classically activated M1 macrophages, and migrate though the dense extracellular matrix to confront pathogens. The ability of monocytes/macrophages to undergo transendothelial migration and invade target tissues depends on podosomes ( Medina et al. , 2015 ).…”
Section: Introductionmentioning
confidence: 99%